Physical activity in people with epilepsy: A systematic review. (12th May 2020) - Johnson, Emma C.; Helen Cross, J.; Reilly, Colin
Abstract: This study aimed to systematically review studies focusing on levels of physical activity (PA) in people with epilepsy (PWE) compared with non‐epilepsy controls, and identify factors associated with PA in PWE. Intervention studies were also reviewed to consider the effects of psychological interventions on levels of PA, and the effects of PA‐based interventions on seizure activity, psychiatric comorbidity, and health‐related quality of life (HRQoL). PRISMA guidelines were followed. Searches were conducted using PubMed, Cochrane Controlled Register of Trials, PsycINFO, and Embase. Forty‐six studies met inclusion criteria, including case‐control, cross‐sectional, and intervention studies. Assessment measures included questionnaires, activity trackers, and measures of physiological fitness. Twelve of 22 (54.5%) case‐control studies utilizing self‐report questionnaire measures reported that PWE were performing lower levels of PA, less likely to be engaging in PA, or less likely to meet PA guidelines than controls. The remaining studies did not find a difference between PWE and controls. Eight of 12 (67%) case‐control studies utilizing exercise/fitness tests reported that PWE performed significantly poorer than controls, whereas in two studies PWE performed better than controls. One of three studies investigating the relationship between PA and seizure frequency found that increased self‐reported PA was associated with having fewer seizures, whereas two did not find a significant relationship. All seven cross‐sectional studies that included measures of HRQoL and depression/anxiety found a positive relationship between levels of PA and HRQoL/reduced levels of depression and anxiety. All four studies that used PA‐based interventions demonstrated improvements in levels of PA and increased HRQoL. Study quality was almost universally low. In conclusion, there is some evidence that PWE engage in less PA than peers, and that interventions can improve PA levels and HRQoL. However, there is a need for more robust study designs to better understand PA in individuals with epilepsy.